SMCHD1 promotes ATM‐dependent DNA damage signaling and repair of uncapped telomeres. (21st February 2020) - Vančevska, Aleksandra; Ahmed, Wareed; Pfeiffer, Verena; Feretzaki, Marianna; Boulton, Simon J; Lingner, Joachim
Abstract: Structural maintenance of chromosomes flexible hinge domain‐containing protein 1 (SMCHD1) has been implicated in X‐chromosome inactivation, imprinting, and DNA damage repair, and mutations in SMCHD1 can cause facioscapulohumeral muscular dystrophy. More recently, SMCHD1 has also been identified as a component of telomeric chromatin. Here, we report that SMCHD1 is required for DNA damage signaling and non‐homologous end joining (NHEJ) at unprotected telomeres. Co‐depletion of SMCHD1 and the shelterin subunit TRF2 reduced telomeric 3′‐overhang removal in time‐course experiments, as well as the number of chromosome end fusions. SMCHD1‐deficient cells displayed reduced ATM S1981 phosphorylation and diminished formation of γH2AX foci and of 53BP1‐containing telomere dysfunction‐induced foci (TIFs), indicating defects in DNA damage checkpoint signaling. Removal of TPP1 and subsequent activation of ATR signaling rescued telomere fusion events in TRF2‐depleted SMCHD1 knockout cells. Together, these data indicate that SMCHD1 depletion reduces telomere fusions in TRF2‐depleted cells due to defects in ATM‐dependent checkpoint signaling and that SMCHD1 mediates DNA damage response activation upstream of ATM phosphorylation at uncapped telomeres. Synopsis: Loss of the telomere binding protein TRF2 leads to chromosome end‐to‐end fusions mediated by non‐homologous end joining. Here, SMCHD1 (structural maintenance of chromosomes flexible hinge domain‐containing protein 1) is demonstrated to promote the ATM‐dependent DNA damage response at TRF2‐deprived telomeres, which is required for the fusion events. SMCHD1 loss prevents telomere fusions in TRF2‐depleted cells. SMCHD1 is required for the ATM‐dependent DNA damage response in TRF2‐depleted cells. SMCHD1 mediates DNA damage signaling activation upstream of ATM phosphorylation at uncapped telomeres. ATR activation in SMCHD1 knockout cells rescues telomere fusion events in TRF2‐depleted cells. Abstract : Fusion of telomeres lacking shelterin protein TRF2 requires the recently‐identified telomeric chromatin component SMCHD1 for induction of ATM‐mediated damage responses, or alternative ATR activation.